Theoretical and experimental research on a new defrosting control strategy based on differential pressure sensor. (November 2022) - Zhu, Junda; Sun, Huan; Liu, Xinghua; Sun, Zhili; Lei, Zhuoya
Highlights: The ideal installation position of the differential pressure sensor is determined. A novel determination method of defrosting start-time is investigated. Pressure Loss Factor (PLF) is calculated only by differential pressure sensor. The PLF detects the change in the amount of frost on the evaporator. The PLF provided accurate defrosting start-times under varied frosting conditions. Abstract: During system operation, frosting of the (heat pump and refrigerating) evaporator is inevitable. As such, the determination of the defrosting start time is integral for maintaining efficient and stable operation of the system. In the present study, a dimensionless parameter, pressure loss factor (PLF), was proposed based on the differential pressure sensor to determine the defrosting start time. For PLF, only the pressure difference before and after the evaporator needs to be measured, allowing for the growth trend of the frost layer on the evaporator to be quantitatively described. Firstly, through preliminary experiments, the optimal layout position of the differential pressure sensor was determined. Subsequently, the optimal defrosting time and PLF start threshold were determined based on the heat transfer rate of the evaporator. Under different experimental conditions, frosting experiments were conducted to validate the reliability of the proposed method. The results reveal that the optimal measuring point of the differential pressure sensor of the evaporator (with double fans) was on the central axis. The average error between the pressure difference at the measuring point and the average pressure difference of the evaporator was 2.76% under different experimental conditions. By using the PLF defrosting control method, the defrosting start time was accurately determined with the maximum error of ±5.5%.